Anti-inflammatory and analgesic activities of the aqueous extracts of Margaritaria discoidea (Euphorbiaceae) stem bark in experimental animal models - Adeolu A Adedapo; Margaret O Sofidiya; Anthony J Afolayan (Revista de Biología Tropical, 2009)
Margaritaria discoidea is a medicinal plant used for the treatment of various body pains in Central, Eastern and Southern Africa. The aqueous extract of its stem bark was investigated for its anti-inflammatory and analgesic activities in animal models. The extract at 50, 100 and 200mg/kg body weight reduced significantly the formation of oedema induced by carrageenan and histamine. In the acetic acid-induced writhing model, the extract had a good analgesic effect characterized by a reduction in the number of writhes when compared to the control. Similarly, the extract caused dose-dependent decrease of licking time and licking frequency in rats injected with 2.5% formalin. These results were also comparable to those of indomethacin, the reference drug used in this study. Acute toxicity test showed that the plant may be safe for pharmacological uses. This study has provided some justification for the folkloric use of the plant in several communities for conditions such as stomachache, pain and inflammations. Rev. Biol. Trop. 57 (4): 1193-1200. Epub 2009 December 01. Margaritaria discoidea es una planta medicinal usada para el tratamiento de varios dolores corporales en la parte sur, central y oriental de África. Se investigaron las propiedades analgésicas y antiinflamatorias de la extracción acuosa de la corteza de su tallo en modelos animales. Los extractos de 50, 100 y 200mg/kg de peso corporal redujeron significativamente la formación del edema inducido por la carragenina y la histamina. En el modelo de contracción abdominal inducida por ácido acético, el extracto mostró un buen efecto analgésico caracterizado por la reducción en el número de contracciones en comparación con el grupo control. El extracto causó una disminución dependiente de la dosis del tiempo y la frecuencia de lamido en las ratas inyectadas con formalina al 2.5%, lo cual evidencia su efecto analgésico. Estos resultados fueron comparables con los de la indometacina, la droga de referencia usada en este estudio. La prueba de toxicidad aguda mostró que la planta podría ser segura para usos farmacológicos. Este estudio proporciona justificación para el uso folclórico de esta plata en varias comunidades, con el objetivo de tratar padecimientos tales como dolor de estómago, dolor e inflamaciones.